(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The current study aims to formulate an anti-hypertensive drug manidipine self-nanoemulsifying drug delivery system (SNEDDS) employing different novel polymers to enhance solubility and drug release manidipine. The optimal concentration of excipients chosen based on solubility study further confirmed by self-emulsification region of pseudo ternary phase diagram. Manidipine SNEDDS optimized employing Box-Behnken Design (BBD) through the study of factors - the amount of capryol 90(A), cremophor RH40 (B) and triacetin (C) and responses -droplet size (Y1), zeta potential (Y2), and cumulative percentage of drug release after 60 min(Y3). All formulations were evaluated for particle size, zeta potential, polydispersity index, entrapment efficiency, drug content, and in-vitro drug release. The optimized formulation was characterized for FTIR, SEM, and stability studies. The study indicates that manidipine optimized formulation MF11 comprising of capryol 90 (40.0%), cremophor RH40 (10.0%) and triacetin (30.0%) exhibited minimum droplet size (76.5 ± 2.87), best zeta potential (-24.7 ± 1.31mV) and entrapment efficiency (98.23 ± 1.74%) content uniformity (99.12 ± 1.28%) maximum drug release (98.79 ± 1.68%). The FTIR studies of MF11 indicated no significant interaction amid the drug and formulation excipients. The SEM data revealed that particle size is in the nanometer range with a zeta potential value >5 mV indicating higher absorption and stability. Accelerated stability studies indicated the formulation to be stable for 3 months. Hence the results revealed that application of SNEDDS formulation technique for manidipine increased solubility and drug release.